The financial crisis and health care systems in Europe: universal care under threat? Trends in health sector reforms in Germany, the United Kingdom, and Spain - Lígia Giovanella; Klaus Stegmüller (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
The paper analyzes trends in contemporary health sector reforms in three European countries with Bismarckian and Beveridgean models of national health systems within the context of strong financial pressure resulting from the economic crisis (2008-date), and proceeds to discuss the implications for universal care. The authors examine recent health system reforms in Spain, Germany, and the United Kingdom. Health systems are described using a matrix to compare state intervention in financing, regulation, organization, and services delivery. The reforms' impacts on universal care are examined in three dimensions: breadth of population coverage, depth of the services package, and height of coverage by public financing. Models of health protection, institutionality, stakeholder constellations, and differing positions in the European economy are factors that condition the repercussions of restrictive policies that have undermined universality to different degrees in the three dimensions specified above and have extended policies for regulated competition as well as commercialization in health care systems.